International Financial Corporation: Annual Report 1990 - International Finance Corporation (Washington DC International Financaial Corporation, 1990)
The International Finance Corporation (IFC) is a multilateral development institution.
osc 20/10/2021
Ref
Keywords: Annual Report; International Finance Corporation